Liver-targeting MRI contrast agent based on galactose functionalized o-carboxymethyl chitosan - Xu, Li; Ren, Zhanying; Li, Guolin; Xu, Danni; Miao, Jiaqian; Ju, Jingxuan; Mo, Xuan; Wang, Xianghui; Deng, Hongping; Xu, Min (Frontiers in Bioengineering and Biotechnology, 2023)
Commercial gadolinium (Gd)-based contrast agents (GBCAs) play important role in clinical diagnostic of hepatocellular carcinoma, but their diagnostic efficacy remained improved. As small molecules, the imaging contrast and window of GBCAs is limited by low liver targeting and retention. Herein, we developed a liver-targeting gadolinium (Ⅲ) chelated macromolecular MRI contrast agent based on galactose functionalized o-carboxymethyl chitosan, namely CS-Ga-(Gd-DTPA)n, to improve hepatocyte uptake and liver retention. Compared to Gd-DTPA and non-specific macromolecular agent CS-(Gd-DTPA)n, CS-Ga-(Gd-DTPA)n showed higher hepatocyte uptake, excellent cell and blood biocompatibility in vitro. Furthermore, CS-Ga-(Gd-DTPA)n also exhibited higher relaxivity in vivo, prolonged liver retention and better T1-weighted signal enhancement in vivo. At ten days post-injection of CS-Ga-(Gd-DTPA)n at a dose of 0.03 mM Gd/Kg, Gd had a little accumulation in liver with no liver function damage. The good performance of CS-Ga-(Gd-DTPA)n gives great confidence in developing liver-specifc MRI contrast agents for clinical translation.